Sistem Pendukung Keputusan Dalam Pemilihan Buah Semangka yang Layak Dijual Menggunakan Metode AHP dan PROMETHEE - Agil Indriyani; Raissa Amanda Putri (Universitas Budi Darma, 2023)
Watermelon and Melon Buying and Selling Twins is a business that exports watermelons and melons to various cities owned by Mr. Kliwon whose address is at Pulau Gambar Village. In the Watermelon and Melon Buying and Selling Twins, in selecting the best quality watermelons suitable for sale, problems were found, namely that usually because they were affected by high prices, farmers did not prioritize the best quality watermelons and only focused on the number of fruits to be sold and agents had difficulty selecting watermelons. The best quality is suitable for sale, especially for export outside the city. So, with this problem, the author took the initiative to solve the problem correctly and maximize the determination of watermelons that are suitable for sale by designing and building a web-based decision support system by applying the AHP and PROMETHEE methods to help agents determine the best quality of watermelon. The design of this web-based application was carried out by conducting research at the Watermelon and Melon Buying and Selling Twins by collecting data on watermelon fruit and criteria data on watermelon fruit. After the data was collected, each fruit was weighted and ranked and then entered into the application that had been built. Based on the calculation results in this research, alternative weighting using the AHP method helps weighting with a weight scale of 1 - 9 according to AHP provisions. After carrying out alternative weighting, the next ranking is using the PROMETHEE method to get the netflow value, ranking 1 is obtained by 15 with a netflow value of 3,583 and Rank 15 is obtained by fruit 5 with a netflow value of -1.833.